Description of Self-Esteem in High School Members of the Extracurricular Paskibra - Prayoga, Arya Dwi; Nastiti, Dwi (Psikostudia : Jurnal Psikologi, 2024)
This research conducted as a response to the phenomenon of PASKIBRA member vocational/high school students experiencing self-esteem problems. The aim of this research to find out the self-esteem of active Extracurricular Paskibra members in Krian District. The population in this study was high school/vocational school students, members of the active extracurricular Paskibra in Krian District, totaling 103 high school/vocational school students.The sample in this study was 103 samples using a saturated sampling technique, namely where the entire population was sampled. The data collection technique in this research uses a psychological scale, namely the self-esteem scale. The self-esteem scale was adopted from the scale compiled by Utari with reference to aspects according to Coopersmith, namely strength, significance, virtuousness, and competence. In this study, the instrument was declared valid (rit > 0.30) and reliable (Cronbach's Alpha = 0.927) using the JASP program version 0.18. The results show that there are 12 students (12%) with low self-esteem in the PASKIBRA extracurricular member student's self-esteem category, however there are 78 students (76%) showing the medium self-esteem category and 13 students (13%) showing the high self-esteem category. Meanwhile, descriptively, the problem of low self-esteem among female students is higher than that of male students.Penelitian ini dilakukan sebagai respons terhadap fenomena pada siswa SMA/SMK anggota PASKIBRA mengalami permasalahan self-esteem. Tujuan dari penelitian ini adalah untuk mengetahui gambaran harga diri pada anggota Ekstrakurikuler Paskibra aktif Kecamatan Krian. Populasi dalam penelitian ini yaitu siswa SMA/SMK anggota Ekstrakurikuler Paskibra aktif Kecamatan Krian berjumlah 103 siswa SMA/SMK. Sampel dalam penelitian ini sebanyak 103 sampel dengan menggunakan teknik sampel jenuh, yakni dimana semua jumlah populasi dijadikan sampel. Teknik pengumpulan data pada penelitian ini menggunakan teknik skala psikologi yakni skala harga diri, yang diadopsi dari skala yang dikembangkan oleh Utari dengan merujuk pada aspek-aspek menurut Coopersmith yaitu kekuatan (power), keberartian (significance), kebaikan (virtue), kemampuan (competence). Dalam penelitian ini Instrumen dinyatakan valid (rit > 0,30) dan reliabel (Cronbach’s Alpha = 0,927) dengan menggunakan bantuan program JASP versi 0.18. Hasil menunjukkan harga diri siswa anggota ekstrakurikuler PASKIBRA terdapat 12 siswa (12%) dengan kategori self-esteem rendah, akan tetapi terdapat 78 siswa (76%) menunjukkan kategori harga diri sedang dan 13 siswa (13%) menunjukkan kategori harga diri tinggi. Sementara itu secara deskriptif permasalahan harga diri rendah siswa perempuan lebih tinggi dibandingkan laki-laki.